Lifestyle factors in Black female breast cancer survivors—Descriptive results from an online pilot study - Connor, Avonne E.; Dibble, Kate E.; Visvanathan, Kala (Frontiers in Public Health, 2023)
Background: Breast cancer (BC) research examining disparities in cancer survivorship and modifiable risk behaviors has been mostly cancer-specific, leaving relevant gaps in disparities research relating to other cancer survivorship outcomes, including cardiovascular disease (CVD). Maintaining healthy lifestyle behaviors is a critical component of successful cancer survivorship, where unhealthy behaviors may increase the risk for recurrence, second primary cancers, and incidence of new comorbid conditions, including CVD. The current study describes BC survivorship factors among an online pilot study of Black BC survivors in Maryland, with a focus on the burden of obesity, comorbidity, and behavioral factors associated with CVD risk. Methods: Utilizing social media recruitment strategies and survivor networks, we recruited 100 Black female BC survivors to complete an online survey. Descriptive characteristics (demographic, clinical, and lifestyle factors) were analyzed in terms of frequencies, means, standard deviations (SD) overall and by county. Results: The average ages at time of survey and at primary BC diagnosis were 58.6 years (SD= 10.1) and 49.1 years (SD=10.2), respectively. More than half of the survivors reported having hypertension (51%); and while only 7% reported being obese at the time of BC diagnosis, 54% reported being obese at the time of survey which was on average 9 years post BC diagnosis. Only 28% of the survivors reported meeting weekly exercise recommendations. While 70% were never smokers, most ever smokers resided in Baltimore City/Baltimore County (n=18 ever smokers). Conclusion: Our pilot study identified at-risk BC survivors in Maryland due to the high prevalence of CVD risk factors (hypertension, obesity, limited exercise). These pilot study methods will inform a future statewide multilevel prospective study to improve health behaviors among Black BC survivors.